Bovine cysticercosis in slaughtered cattle as an indicator of Good Agricultural Practices (GAP) and epidemiological risk factors - Marques Rossi, Gabriel Augusto [UNESP]; Lux Hoppe, Estevam Guilherme [UNESP]; Mathias, Luis Antonio [UNESP]; Centola Vidal Martins, Ana Maria; Mussi, Leila Aparecida; Prata, Luiz Francisco [UNESP] (Elsevier B.V., 2015)
This study focused on estimating the economic losses resulting from cysticercosis at beef cattle farms that supply an export slaughterhouse located in the state of Sao Paulo, Brazil, and to identify the epidemiological risks factors involved in the disease to ascertain if these farms adopt Good Agricultural Practices (GAP). To this, we used data recorded in 2012 by Brazil's Federal Inspection Service (SIP) on the daily occurrence of the disease, according to the farm from which the animals originated. In addition, the associated risk factors were determined based on a case-control study at 48 farms. Cysticercosis was detected in 2.26% (95% CI 2.2-2.33) of the 190,903 bovines supplied by 556 farms in the following four states: 2.92% (95% CI 2.83-3.03) in Sao Paulo, 1.81% (95% CI 1.71-1.93) in Minas Gerais, 0.71% (95% CI 0.6-0.82) in Goias and 1.11% (95% CI 0.79-1.57) in Mato Grosso do Sul, with significant differences in the epidemiological indices of these states. Cysticercosis was detected at 58.45% (95% CI 54.36-62.55) of the farms of this study, representing estimated economic losses of US$312,194.52 for the farmers. Lower prevalence of this disease were found at the farms qualified for exports to the European Union, indicating a statistically significant difference from those not qualified to export to Europe. The access of cattle to non-controlled water sources, as well as sport fishing activities near the farms, was identified as risk factors. Cysticercosis causes considerable losses in Brazil's beef supply chain, with lower prevalence appearing only at farms qualified to export to the European Union. As for the access of cattle to non-controlled water sources, this is an indication that GAP are not implemented by some farms, demonstrating the violation of international agreements by the industry and the farms. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Epidemiology; Beef sanitary inspection; Taenia saginata; Zoonosis